MODEL EKUITAS MEREK PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN SIM CARD - Yuliana, Yayuk; Putra, Mardi Giwa (Aksara Public, 2018)
This purpos aims to determine: Influence Brand Equity to Purchase Decision sim card. Research method with quantitative descriptive approach.. Independent variables in this research are Brand Awareness, Brand Associations, Perceived Quality, Brand Loyalty and the dependent variable is Purchasing sim card decision. Data collection using questionnaires with a total sample of 100 respondents who are buyers and users sim card card prime card. Data analysis using multiple linear regression. Partial research results obtained three variables that are partially significant that the brand association (X2) with a probability significance value Î± of 0,000 <0.05 units of tcount> ttable is 8.871 > 0,1996, perceived quality (X3) with probability significance value Î±, 000 0,000 <0,05 while the tcount value is 5,549> 1,96 and brand loyalty (X4) with value of probability Î± equal to 0,002 <0,05 while value thitung> ttable is 3.249> 1.96.